2022
DOI: 10.5267/j.ijdns.2022.4.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of big data on decision quality: Evidence from telecommunication industry

Abstract: The aim of the research is to test the impact of big data on the quality of decision making. The necessary data was collected from telecommunication companies operating in Jordan. Three companies provide telecommunications services in Jordan: Zain, Umniah, and Orange. Non-probability purposive sampling was used. Hence, the study instrument was distributed to managers at the senior and middle levels of these companies. The structured equation modeling (SEM) technique was employed to test the study hypotheses. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…The third question: Is there a relationship between the maturity of big data and the value of big data for information technology specialists in the telecommunications sector in the Republic of Yemen? 1-Testing the relationships between the axes and the two scales: Using the Pearson correlation coefficient between all the axes with each other and each of the Big Data Maturity Scale and the Big Data Value Scale, it was found that there is a positive and statistically significant direct relationship between the two scales and all axes, at a significance level of less than 0.05, as shown in the following table: Table (4) shows the correlation between each of the dimensions of the independent variable (maturity of big data) with the dimensions of the dependent variable (the value of big data). In general, there was a positive and statistically significant direct correlation between the variables and dimensions, at a level of significance not less than (0.05).…”
Section: Fig 3 the Results Of The Value Of Big Datamentioning
confidence: 99%
“…The third question: Is there a relationship between the maturity of big data and the value of big data for information technology specialists in the telecommunications sector in the Republic of Yemen? 1-Testing the relationships between the axes and the two scales: Using the Pearson correlation coefficient between all the axes with each other and each of the Big Data Maturity Scale and the Big Data Value Scale, it was found that there is a positive and statistically significant direct relationship between the two scales and all axes, at a significance level of less than 0.05, as shown in the following table: Table (4) shows the correlation between each of the dimensions of the independent variable (maturity of big data) with the dimensions of the dependent variable (the value of big data). In general, there was a positive and statistically significant direct correlation between the variables and dimensions, at a level of significance not less than (0.05).…”
Section: Fig 3 the Results Of The Value Of Big Datamentioning
confidence: 99%
“…Because digital supply chains employ tools of great value that help organizations mitigate wastage in manufacturing processes. Several previous studies confirmed that there is a gap in studies examining the relationship between digital transformation technologies and the application of lean manufacturing strategies in industrial companies (Gjeldum et al, 2016;Kolberg et al, 2017;Al-Alwan et al, 2022;Landscheidt & Kans, 2016). Accordingly, the study hypothesis can be formulated as follows:…”
Section: Digital Supply Chain and Lean Manufacturingmentioning
confidence: 85%
“…Digital transformation refers to "the increasing prevalence of digital technologies in society and the associated changes in people's communication and behaviour" (Gimpel et al, 2018). It creates new opportunities for organizations and supply chain practices (Al-Alwan et al, 2022;Tariqa et al, 2022a;Eldahamsheh et al, 2021). The fourth-generation industrial revolution through digital transformation allows organizations to achieve high flexibility when formulating their supply chain strategies and practices, thus creating greater organizational value (Tariq et al, 2022b;Büyüközkan and Göçer 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since digitization is an important component of the success of supply chains in the current business environment, companies seek to adopt and use industry 4.0 technologies. But before that, barriers of adopting Industry 4.0 technologies must be explored (Al-Alwan et al, 2022;Fernando et al, 2022). According to Raj et al (2020), investigating the barriers of Industry 4.0 adoption and implementation is still uncultivated in the literature.…”
Section: Introductionmentioning
confidence: 99%